Thermodynamic effect of ammonium based ionic liquids on CO2 hydrates phase boundary - Khan, M.S. (Elsevier B.V., 2017)
In this experimental study, the phase boundary behavior of CO2 hydrate is reported in the presence of 1, 5, and 10 wt of three aqueous ammonium based ionic liquids (AILs) solutions. The T-cycle technique is used to measure the hydrate equilibrium conditions of AILs + CO2 + H2O hydrate systems within the ranges of 274–283 K and 1.80–4.20 MPa. All studied AILs inhibited CO2 hydrate with the inhibition effect increasing with AILs concentration. The 10 wt, TEAOH showed the highest inhibition effect with an average suppression temperature (∆ Ŧ) of 1.7 K, followed by TMACl (∆ Ŧ = 1.6 K) and then TPrAOH (∆ Ŧ = 1.2 K). Furthermore, COSMO-RS analysis is performed to understand the molecular level inhibition mechanism of AILs. In addition, the enthalpies of hydrate dissociation for all studied systems are also determined. The calculated hydrate dissociation enthalpies revealed that all the studied AILs show insignificant participation in CO2 hydrate cage formation at all concentrations, hence, do not form semi-clathrate hydrates. © 2017 Elsevier B.V.